The body in the bookstore - Alexander, Ellie (Secret bookcase mystery, 2024)
"Bookseller Annie Murray is thrilled when the mystery-themed book festival she sets up to revive the dwindling fortunes of her workplace and sanctuary seems poised for success. But events take a shocking turn when a body is discovered hidden behind the shelves, and it's revealed that the victim is Annie's old college acquaintance. Determined to ensure the festival's success and save the small town of Redwood Grove from a killer, Annie begins piecing together clues with the help of her friends. But as the list of suspects grows longer - a local boutique-owner, an envious old classmate, a bitter ex-boyfriend - Annie is drawn deeper into the case. With the aid of her old criminology professor-turned-detective, can Annie unmask the murderer before they turn her festival into a real-life whodunit?" -- Back cover.